Rosuvastatin Synergistically Enhances the Antinociceptive Efficacy of Duloxetine in Paclitaxel-Induced Neuropathic Pain in Mice - Hernandez-Kunstmann, A; Constandil-Cordova, L; Pelissier, T (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
Paclitaxel, a widely used cancer chemotherapeutic agent, has high incidence of neurotoxicity associated with the production of neuropathic pain, for which only duloxetine has shown significant but moderate analgesic effect. Since statins, classically used to reduce hypercholesterolemia, have shown antinociceptive effect in preclinical studies on neuropathic pain, we studied whether the antinociceptive efficacy of duloxetine could be synergistically potentiated by rosuvastatin in a model of paclitaxel-induced neuropathy in mice. The astrocytic and microglial responses in the spinal cord of paclitaxel-treated mice were also assessed by measuring GFAP and CD11b proteins, respectively. Paclitaxel treatment did not impair motor coordination and balance in rotarod testing. Rosuvastatin, duloxetine, and the rosuvastatin/duloxetine combination (combined at equieffective doses) dose-dependently decreased mechanical allodynia (ED30, von Frey testing) and thermal hyperalgesia (ED50, hot plate testing) in paclitaxel-treated mice. Isobolographic analysis showed a superadditive interaction for rosuvastatin and duloxetine, as both the ED30 and ED50 for the rosuvastatin/duloxetine combination contained only a quarter of each drug compared to the individual drugs. The rosuvastatin/duloxetine combination reversed paclitaxel-induced GFAP overexpression, indicating that such effects might depend in part on astrocyte inactivation. Results suggest that statins could be useful in synergistically enhancing the efficacy of duloxetine in some chemotherapy-induced neuropathic conditions. © 2023 by the authors.